EDUKASI LITERASI DIGITAL : PENDAMPINGAN TRANSFORMASI DIGITAL PELAKU UMKM SUKABUMI PAKIDULAN - Teddy Setiawan; Dwinanto Priyo Susetyo; Eka Pranajaya (Bajang Institute, 2021)
The urgency of encouraging MSMEs to transform from conventional to digital businesses using various digital platforms is increasingly urgent because digital technology continues to develop rapidly. The problem that occurs today is that literacy and ability in the digital field are not evenly distributed so that there are still many MSME actors who have not been able to use digital technology to the fullest. The digital literacy gap of MSME actors in Sukabumi Pakidulan allows academics to provide assistance, education and training on a regular basis. The method of implementing this PKM activity refers to the results of direct observations that have been carried out by the service team at the community service location. The increased understanding and ability of participants in the field of digital literacy has provided additional broader insights about the online market network even though they are new to social media. the ability to do online marketing through social media can open their awareness and courage to venture into digital eCommerce platforms and marketplaces, including transactions and financing carried out by fintech, and so on to support their marketing activities that are more developed and upscale.